SECOND LANGUAGE ACQUISITION: KRASHEN’S MONITOR MODEL AND THE NATURAL APPROACH - Hajimia, Hafizah; Singh, Manvender Kaur Sarjit; Chethiyar, Saralah Devi Mariamdaran (PEOPLE: International Journal of Social Sciences, 2020)
The second language can be defined as any other language which is learned or acquired after their first language or their mother tongue. Learning or acquiring a second language can be a difficult task for anybody that wishes to speak or write in a language other than their first language. Teachers should have the basic knowledge of second language acquisition theories to provide a comprehensive teaching and learning environment to students. One of the most applied and well-accepted theories is Stephen Krashen’s theory of second language acquisition. The present study was carried out as an observation on students to address the importance of Krashen’s Monitor Model and the Natural Approach in the stages of second language development to ensure effective teaching of the second language. The findings show that the cause of the input factor should be taken into consideration when teaching a second language/foreign language. The findings also indicated that cooperative learning can be a good method for students to get comprehensible input from their classmates.